2001
DOI: 10.1001/archinte.161.13.1660
|View full text |Cite
|
Sign up to set email alerts
|

Race and Sex Differences in Consistency of Care With National Asthma Guidelines in Managed Care Organizations

Abstract: Even among patients with health insurance, disparities in asthma care for African Americans compared with whites exist and may contribute to race disparities in outcomes. Women generally reported better asthma care but may benefit from greater use of inhaled corticosteroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 122 publications
(60 citation statements)
references
References 51 publications
2
57
1
Order By: Relevance
“…Taken together, these observations suggest a gap in out-of-hospital asthma deaths by race (i.e., black patients were more likely to die of asthma exacerbations out-of-hospital than white patients). Potential explanations include difficulties in accessing adequate healthcare (26), poor preventative management practices (e.g., nonadherence) (27,28), and delays in seeking medical attention (29,30), which are known to be more common among blacks compared with whites in the United States. These considerations suggest that the subset of patients hospitalized for asthma exacerbations may not be representative of all patients with severe and potentially life-threatening exacerbations.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these observations suggest a gap in out-of-hospital asthma deaths by race (i.e., black patients were more likely to die of asthma exacerbations out-of-hospital than white patients). Potential explanations include difficulties in accessing adequate healthcare (26), poor preventative management practices (e.g., nonadherence) (27,28), and delays in seeking medical attention (29,30), which are known to be more common among blacks compared with whites in the United States. These considerations suggest that the subset of patients hospitalized for asthma exacerbations may not be representative of all patients with severe and potentially life-threatening exacerbations.…”
Section: Discussionmentioning
confidence: 99%
“…However, this finding also may represent physician bias in the management of patients belonging to different racial/ethnic groups, which has been observed in several prior studies in the adult population. [33][34][35][36] Although adjusted results indicated fewer bacterial diagnoses for African American and Latino patients, compared with non-Hispanic white patients, this did not translate to lower adjusted rates of receiving antibiotics. This may indicate that these groups were more likely to receive antibiotics for inappropriate indications (ie, nonbacterial illnesses).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in the physical health sector demonstrated poorer compliance among minority adults in the treatment of HIV (Mehta et al, 1997) and renal disease (Curtin et al, 1999) and among minority children in the treatment of asthma (Krishnan et al, 2001), even after adjusting for factors such as age, education, employment, access to insurance, and symptom frequency (Krishnan et al, 2001). Similarly, adherence may also relate to the ability of consumers and providers to communicate with one another.…”
Section: Discussionmentioning
confidence: 99%